Enhancement sensitivity of TRPV1 in dorsal root ganglia via the SP-NK-1 pathway contributes to increased bladder organ sensitivity caused by prostatitis - Jiang, ZhiPeng; Luo, Wen; Liu, Lei; Long, ZongMin (Frontiers in Neuroscience, 2024)
Chronic prostatitis/chronic pelvic pain syndrome is a prevalent condition affecting the male urinary system. The urinary dysfunction resulting from this disorder has a direct or indirect impact on the patient’s quality of life. Recent studies have suggested that organ cross-sensitization between the prostate and bladder may elucidate this phenomenon; however, the specific molecular mechanisms remain unclear. In this study, we simulated the urinary symptoms of prostatitis patients using an animal model and examined the expression of relevant proteins within the prostate-bladder sensitized neural pathway. We found that transient receptor potential vanilloid 1 (TRPV1) protein is highly expressed in the dorsal root ganglia (DRG) that co-innervate both the prostate and bladder, potentially increasing the sensitivity of TRPV1 channels via the substance P-neurokinin 1 (SP-NK-1) pathway, which may exacerbate micturition symptoms. Furthermore, in the absence of bladder inflammation, elevated levels of neurogenic substances in bladder tissue were found to sensitize bladder sensory afferents. Collectively, these results underscore the significant role of TRPV1 in bladder sensitization associated with prostatitis, suggesting that the inhibition of TRPV1 along this sensitization pathway could be a promising approach to treating urinary dysfunction linked to prostatitis in the future.